Phenolic Distribution in Liquid Preparations of Vaccinium myrtillus L. and Vaccinium vitis idaea L. Issue 5 (19th July 2013) - Ieri, Francesca; Martini, Sara; Innocenti, Marzia; Mulinacci, Nadia; de, Victor; Comte, Gilles; Santos‐Buelga, Celestino
ABSTRACT Introduction Liquid preparations such as tinctures and 'bud extracts' of bilberry and lingonberry are typical products used in some European countries but they have not been widely studied to date. Objective Our aim was to define a phytochemical profile in terms of phenolic compounds for liquid preparations of Vaccinium myrtillus L. (bilberry) and Vaccinium vitis idaea L. (lingonberry) foliar tissues, and evaluate their stability. Methods Up to 17 extracts of lingonberry, and bilberry have been analysed by HPLC equipped with a diode‐array detector (DAD) in combination with MS. Some of these samples were freshly prepared (laboratory extracts). Results Phenolic profiles of the bud extracts and tinctures of bilberry and lingonberry were obtained at 330 nm, typical of the cinnamoyl compounds and suitable to distinguish these two species. Analogously, the profiles at 280 nm were used to detect the arbutin derivatives recognised as the typical markers of lingonberry leaves only. Among the cinnamoyl derivatives, chlorogenic acid was the main compound found in bilberry samples, while caffeoyl arbutin was the principal marker in lingonberry samples. In quantitative terms, the hydroxycinnamic acids were the main class in bilberry bud extracts ranging between 4.67 and 6.81 mg/L (from 52 to 84% of the total phenols). The young sprouts of this species, independently from the extraction mixture, show a higher phenolic content than adult leaves of the same plant. Conclusions The analytical method allowed to define fingerprints of bilberry and lingonberry liquid preparations. Moreover, without applying accelerated ageing protocols, the stability over time of 11 samples was evaluated up to 6 months, demonstrating negligible variations. Copyright © 2013 John Wiley & Sons, Ltd.